Prevention of Capsular Contracture Using Leukotriene Antagonists. Issue 5 (November 2015) - Graf, Ruth; Ascenço, Adriana S. K.; Freitas, Renato da S.; Balbinot, Priscilla; Peressutti, Carolina; Costa, Diogo F. B.; dos Santos, Fábio de H. C. R.; Ratti, Marco A. S.; Kulchetscki, Rodrigo M.
Abstract : Background: Capsular contracture is a common occurrence in plastic surgery, with a prevalence varying from 0.5 percent up to 30 percent. Although the standard treatment is capsulectomy, alternative treatments have been studied, such as the use of leukotriene inhibitors. These drugs have recently been evaluated in the prophylaxis of contracture. The authors aimed to assess the efficacy of montelukast (Singulair) in the prevention of capsular contracture in patients undergoing mammaplasty with textured silicone prostheses. Methods: The authors followed 82 patients (164 breasts) for a minimum of 2 years. Of these, 37 were administered montelukast. Results: The number of affected patients and the severity were higher among the 45 patients who did not use montelukast. Conclusion: The prophylactic use of Singulair was, in this sample, shown to be effective in helping to reduce the incidence of capsular contracture. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.